2023
DOI: 10.1007/s12144-023-04518-z
|View full text |Cite
|
Sign up to set email alerts
|

“The many faces of sorrow”: An empirical exploration of the psychological plurality of sadness

Abstract: Sadness has typically been associated with failure, defeat and loss, but it has also been suggested that sadness facilitates positive and restructuring emotional changes. This suggests that sadness is a multi-faceted emotion. This supports the idea that there might in fact be different facets of sadness that can be distinguished psychologically and physiologically. In the current set of studies, we explored this hypothesis. In a first stage, participants were asked to select sad emotional faces and scene stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…We showed that when own-culture emotional faces were presented with backward masking for 33.33 ms and assessed with unbiased criteria for signal detection and discrimination performance, participants could correctly identify a presented face only when conscious perception was involved. These findings were replicated in our research in the past five years , 2020bTsikandilakis, Yu, et al 2021a;Tsikandilakis, Leong, et al, 2021;Tsikandilakis, Bali, Yu, et al, 2023;Tsikandilakis, Bali, Karlis, et al 2023a, 2023b.…”
supporting
confidence: 83%
“…We showed that when own-culture emotional faces were presented with backward masking for 33.33 ms and assessed with unbiased criteria for signal detection and discrimination performance, participants could correctly identify a presented face only when conscious perception was involved. These findings were replicated in our research in the past five years , 2020bTsikandilakis, Yu, et al 2021a;Tsikandilakis, Leong, et al, 2021;Tsikandilakis, Bali, Yu, et al, 2023;Tsikandilakis, Bali, Karlis, et al 2023a, 2023b.…”
supporting
confidence: 83%
“…Loss Concerns: suggest recognizing that a resource is lost and seeking new resource to replace it (e.g., disappointment, sadness, grief) ( Draper, 1999 ; Freed and Mann, 2007 ; Zeelenberg et al, 2000 ; Chua et al, 2009 ; Horwitz and Wakefield, 2007 ; Lench et al, 2016 ; Averill, 1968 ; Bonanno and Kaltman, 2001 ; Archer, 1999 ; Shear and Shair, 2005 ; Kübler-Ross and Kessler, 2005 ; Parkes, 2013 ; Neimeyer et al, 2014 ; Fuchs, 2018 ; Bonanno, 2019 ; Arias et al, 2020 , this issue; Tsikandilakis et al, 2023 )…”
Section: The Human Affectome: What Are Human Affective Phen...mentioning
confidence: 99%
“…For example, we have previously provided evidence that anger and hostility have different psychophysiological, facial-expressive and emotional-intentional characteristics, and that these effects includedamong other contributing variables (see particularly Adler, 2014)gender differences for the perception of anger and hostility (Tsikandilakis et al, 2020b). Conversely, and looking at the larger picture of emotional perception and misperception, we have demonstrated that sadness involves emotional subcategories with distinguishable psychophysiological characteristics and distinct eliciting circumstances, i.e., melancholy, misery, bereavement and despair (Tsikandilakis et al, 2023a). Other research groups have claimed to have conceptually been able to separate the six basic emotions, that are commonly used in relevant research, i.e., fear, anger, happiness, sadness, surprise and disgust (see Ekman & Cordaro, 2011; see also Wolf, 2015), to more than one-hundred distinguishable emotional states, including love, jealousy, admiration, trust, anticipation, guilt, contentment, calmness and rejection (see for example Barret et al, 2019;.…”
Section: Discussionmentioning
confidence: 63%